An integrated model: marital effect on adolescent behavioral problems through siblings - Li, Zhaoyi; Zhao, Yunyan; He, Ran; Luo, Rui; Luo, Yuhan; Yang, Zhengqian; Qi, Mengdi; Chen, Fumei (Frontiers in Psychology, 2024)
Few studies have simultaneously focused on the effects of marital conflict and marital intimacy on adolescent development, and little is known about the role of sibling relationships. Thus, this study examined the association between marital relationships and adolescent behavioural problems, including depressive symptoms and aggressive behaviour. At the same time, we explored the mediating role of sibling hostility and sibling affection and the moderating effect of birth order in multichild families in China. Participants included 842 adolescents (Mage = 12.60, 46.2% boys) from Henan Province. Marital relationship, sibling relationship, birth order, depressive symptoms and aggressive behaviour were assessed by a self-administered questionnaire. SEM was then used to examine the role of sibling relationships and birth order in the association between marital relationship and adolescent behavioural problems. Our results showed that marital intimacy was negatively correlated with depressive symptoms and aggressive behaviour, while marital conflict was positively correlated with them. Marital intimacy was associated with depressive symptoms and aggressive behaviour through both sibling hostility and sibling affection. Marital conflict was indirectly associated with depressive symptoms and aggressive behaviour through sibling hostility. In addition, the first-born adolescents were more sensitive to marital intimacy. Given that the occurrence of adolescent behavioural problems is more common in contemporary society, our findings suggest that establishing a more intimate and warmer family atmosphere and promoting positive interactions between siblings may help control adolescent mental health problems.Adolescence is a critical time for the onset and development of behavioural problems, including internalizing problems, such as depressive symptoms, and externalizing problems, such as aggressive behaviour (Blain-Arcaro and Vaillancourt, 2017;Murray et al., 2022). Depressive